Merging kinetic resolution with C–H activation: an efficient approach for enantioselective synthesis. Issue 18 (19th April 2021) - Sumit; Chandra, Devesh; Sharma, Upendra
Abstract : This review summarizes the recent advancements in transition-metal (TM) catalyzed enantioselective C–H activation via kinetic resolution approach. Abstract : In the last two decades tremendous progress has been made in transition-metal (TM)-catalyzed C–H bond functionalization, paving the way to design complex molecules. Despite significant advances, enantioselective C–H activation is still in the age of infancy. For the enantioselective synthesis, several TM catalyst based approaches are well known, including kinetic resolution (KR) and its advanced versions [dynamic kinetic resolution (DKR) and parallel kinetic resolution (PKR)]. These strategies have recently been successfully applied synergetically with the TM catalyzed C–H activation to achieve enantioselective synthesis in a more economical and sustainable way. This review will summarize the recent advancements made towards merging KR with TM-catalysed C–H activation for enantioselective synthesis.